DEATH AND FUNERAL PRACTICES IN RUSSIA. - Mokhov, Sergeĭ. ([Place of publication not identified] : ROUTLEDGE, 2021)
Built on original ethnographic research conducted by the author, this book offers a highly detailed and comprehensive account of funerary history and practices in Russia. Death and Funeral Practices in Russia provides rich data on mortality statistics, trends in the funeral market in contemporary Russia, the legal framework of funerary practices, as well as regional and demographic disparities. The first part of the book presents an in-depth account of the historical development of funerary practice in Russia, charting the emergence and evolution of funeral traditions and customs in the country from the Russian Empire to the collapse of the USSR. Having explored the wider historical context surrounding funerary culture in Russia, the second part of the book explores the key features of the funeral industry in post-Soviet times, highlighting critical changes and areas of continuity. Topics explored include the death care industry in Russia, the key features of the typical funeral in the country, cemetery and crematorium provision, the technicalities and legalities of burial and cremation, and the illegal practices within the funeral market. A truly unique offering, the book is essential reading for academics, policy makers and practitioners interested in the history, legal, technical and professional aspects of the funerary industry in Russia.
OCLC-licensed vendor bibliographic record.
Keywords: Funeral rites and ceremonies -- Russia; Funeral rites and ceremonies -- Soviet Union; Funeral rites and ceremonies -- Russia (Federation); Death care industry -- Russia (Federation) -- History; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Small Business